IEEE GLOBECOM 2007-2007 IEEE Global Telecommunications Conference 2007
DOI: 10.1109/glocom.2007.416
|View full text |Cite
|
Sign up to set email alerts
|

Lightpath-Level Protection versus Connection-Level Protection for Carrier-Grade Ethernet in a Mixed-Line-Rate Telecom Network

Abstract: Ethernet is a success story in Local Area Networks (LAN). Efforts for extending its boundaries beyond LAN to the carriers' backbone networks are in progress. We study the problem of designing reliable and cost-efficient high-rate (100 Gbit/s) carrier-grade Ethernet in a multi-line-rate telecom network under signal transmission-range constraints. Reliability is achieved using shared-path protection at two levels: (1) Protection-at-Connection (PAC) level, or (2) Protection-at-Lightpath (PAL) level. We study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Several approaches based on network topology information like highest nodal degree for sparse node or G-node selection was proposed in [2]. Simple other heuristics like random and nodes with highest bypass traffic were chosen for grooming [2] and have been shown that optimal performance near to full grooming can be achieved using sparse grooming in the same network keeping the other resources like wavelengths etc. constant.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Several approaches based on network topology information like highest nodal degree for sparse node or G-node selection was proposed in [2]. Simple other heuristics like random and nodes with highest bypass traffic were chosen for grooming [2] and have been shown that optimal performance near to full grooming can be achieved using sparse grooming in the same network keeping the other resources like wavelengths etc. constant.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the previous work done in full grooming network is assumed to have traffic grooming capabilities [1]. Research done in sparse grooming, attempts to find the locations of grooming sites [2] [10].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations